“Relative concerns for consumption at the top”: An intertemporal analysis for the UK - Quintana-Domeque, C; Wohlfart, J (Elsevier, 2016)
This paper investigates whether the consumption of rich households provides a reference point in the intertemporal consumption choices of non-rich households. Using UK household data on food consumption, we estimate the Euler equation implied by a life-cycle model incorporating relative concerns for the consumption of rich households. According to both our OLS and GMM estimates, for the population of non-rich households as a whole, there is no evidence of such relative concerns. We also examine an alternative model of relative concerns in which households overconsume when exposed to higher reference group consumption, and find correlational evidence that this may be the case for food consumed away from home. Finally, we investigate the presence of heterogeneous relative concerns (across county and household characteristics) in both models, finding evidence of relative concerns (for consumption at the top) in counties with relatively low income inequality. This mechanism seems to operate for food consumed away from home.